Comparison of sugar content, mineral elements and antioxidant properties of Heterotrigona itama honey from suburban and forest in Malaysia - Zulhilmi Cheng, Mohamad Zulhafiz Shafiq (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: In Malaysia, Heterotrigona itama sp. (stingless bee) industries start to grow rapidly since 2015 but the study on its health benefit is still lacking. This study was aimed to analyse and compare the sugar content, minerals and antioxidant properties of stingless bee honey collected from forest and suburban area in Malaysia. Methods: Sugar content was determined by HPLC, minerals and heavy metals was determined by Inductively Coupled Plasma Optical Emission Spectrometer (ICP-OES) and Atomic Absorption Spectrometer (AAS), total phenolic content (TPC) and total flavonoid content (TFC) by Folin-Ciocalteu and aluminium chloride colorimetry method, respectively. For determining the antioxidant activity of the samples, 2,2-diphenyl-1-(2,4,6-trinitrophenyl) hydrazyl (DPPH), 2,2’-azi-no-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) and ferric reducing antioxidant power (FRAP) assay were used. Results: Fructose, glucose and sucrose are found in all samples in range of 16.03-33.13 g/100g, 8.63-20.72 g/100g and 2.68-34.04 g/100g, respectively. Potassium and sodium were major minerals in all stingless bee honey with an average of 622.36 and 496.01 mg/kg, respectively. Sample from the forest (Sibu, F2) has the highest TPC and TFC with value 520.663±8.119μg GAE/g and 443.25±18.194μg RE/g, respectively. The higher antioxidant activities (DPPH, ABTS, FRAP) also found in samples collected from the forest (F2) with 602.15±12.7 μg TE/g, 575.18±9.38 μg TE/g and 641.36±42.11μg TE/g, respectively. Conclusion: All stingless bee honey studied shown a significant amount of important minerals and antioxidant properties with samples from forest clearly shown significantly higher TPC and TFC as well as the antioxidant activity than samples collected from the suburban area.